VERNAKULARISASI ALQURAN DI TATAR BUGIS:: Analisis Penafsiran AGH. Hamzah Manguluang dan AGH. Abd. Muin Yusuf terhadap Surah al-Ma>‘u>n - Nur, Moh. Fadhil (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2019)
Exploration of religious life and islamic culture in Buginese tribe cannot be separated from vernacularization process. It is an effort to discuss the islamic teaching (al-Qur’an) in the form of translating and writing process into local languages and scripts. The qur’anic commentaries (Tafsir) on the Buginese tribe are written in the Lontaraq languages and script. Most scientific research of Tafsir works related to epistemology and methodology, but do not including elements of Buginese culture. Therefore, this research tries to interpret it more. Based on AGH Hamzah Manguluang and AGH Abd Muin Yusuf investigation and interpretation on surah al-Ma>‘u>n, there are two main topics in Buginese elements, namely: 1) Theology, including: explanation of the existence of Allah, human attitude toward Allah, and the communication forms with Allah SWT and the Prophet Muhammad SAW. 2) Character and social-society, including: human classification and attitude of Buginese society in the context of social community. The placement of culture elements as references in elaborating on the massages of the Holy Qur’an is an attempt to understand the cultural-contextual nature of Holy massages of the Qur’an.